Study of possibility physical interactions antimalarial combination drugs - Timbul Partogi H. Simorangkir (MDPI AG, 2020)
Identification of solid state to investigate the possibility of physical interaction between Antimalarial Artemisinin Combination Treatment base Artesunate (AS) and Amodiaquine (AQ) by hot contact method Kofler, cold contact method (crystallization reaction) and binary phase diagram confirmation had been carried out. The results of hot contact method Kofler shown the formation a new crystalline habit as a long and thin needle on the contact zone (mixing zone) between AS and AQ. A different melting point was seen in its single component. Cold contact methods between two of supersaturated solution of component AS and AQ in methanol solvent also indicated the growth of crystal habit as similar as hot contact method Kofler. Confirmation by biner phase diagram shown the specific diagram for cocrystalline phase. Solid state interaction between AS and AQ was analysed by powder X-ray diffraction, FTIR (Fourier Transformed Infra Red) spectrophotometric, microscopic SEM (Scanning Electron Microscopic) and thermal DTA (Differential Thermal Analysis), TG-DSC (Thermal Gravimetry- Differential Scanning Calorimetry). Microscopic analysis by SEM showed significantly the change of habit and morphology of crystal to long and thin needle shaped. The difference of powder X-ray diffraction (PXRD) interferences peaks were observed in addition to PXRD interference peaks of each component and its physical mixtures that proved formation of cocrystalline phase. DSC Thermogram indicated a new endothermic peak corresponding to melting point of a new cocrystalline phase at temperature 160,4°C.